Wind effects on structures : modern structural design for wind - Simiu, Emil; Yeo, DongHun (John Wiley & Sons, 2019)
"The typical process by which engineered buildings are designed for wind loads in current practice has serious shortcomings. This is due to the inadequate pressure measurement technology and computational resources at the time of its development, and to an ineffective framework for the cooperation between wind and structural engineers. As a result, independent estimates of wind forces on major tall buildings performed in the early 2000s by prominent wind engineering laboratories were found to differ from each other by over 40 %. This finding, and similar findings reported in the literature, prompted intense research efforts that, along with the development of the pressure scanner, led to major advances in the state of the art. However, these advances have not yet been integrated effectively into design practice"--